Analysis of the Influence of Contamination in Lubricant by Biodiesel in a Pin-On-Disk Equipment - Cuerva, Murilo Parra; Gonçalves, Aparecido Carlos [UNESP]; Da Consolação Fonseca de Albuquerque, Maria [UNESP]; Chavarette, Fábio Roberto [UNESP]; Outa, Roberto; De Almeida, Estevão Fusaro [UNESP] (FapUNIFESP (SciELO), 2022)
The introduction of biodiesel to commercial diesel is being increased every year. The need to check this addition to the engine and lubricant is important for automakers and internal combustion engine manufacturers. The oil analysis technique is a type of predictive maintenance, done by collecting oil from equipment and analyzing it later in the laboratory, or by analyzing it directly and continuously in on-line systems. In internal combustion engines, all parts have a pre-established service life, longer or shorter, according to the specific function assigned to it. By analyzing the oil, the condition of these parts can be monitored. The oils analysis reveals the first signs of wear of a component. The identification is made based on the study of the number of particles, size, shape and composition thereof, present in the lubricant samples, which provide accurate information about the conditions of the moving surfaces without the need to disassemble the assembly to which these parts belongs. In this work a lubricant contamination by biodiesels were made to simulate possible scenarios within an internal combustion engine.The lubricant recommended by an engine manufacturer was contaminated with commercial diesel and with different percentages and types of biodiesel. After this contamination they were placed in a pin on disk device under certain conditions.Through the analyzes of the lubricants extracted from the Pin on disk Equipment after the tests, some analysis were carried out in order to study the effects of using biodiesel in the internal combustion engine.These analyzes consisted of Flash point, analytical ferrography, monitoring of ferrous particles generated, viscosity, viscosity index, basicity index and X-ray spectrometry.Among the results obtained it is observed that for a 5% contamination of animal biodiesel there was an increase in the viscosity index. Conversely, the contamination of 5% of animal + vegetable biodiesel decreased the viscosity index in relation to Diesel B5. We also found that these biodiesel additions were not detrimental to the engine and lubricant at the mix ratios and test conditions used.
Keywords: Biodiesel; Diesel internal combustion engines; Lubricant analysis; PIN-ON-DISK; Predictive maintenance; Wear particles